Penggembalaan Kepada Orang Tua yang Lanjut Usia Berdasarkan Yesaya 46:4 - Pheter Simangunsong; Rogate Artaida Tiarasi Gultom; Ibelala Gea (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This writing aims to determine efforts to prevent feelings of loneliness and fear of death in the elderly. Elderly people are more likely than young people to feel lonely and afraid of death. The elderly are closely related to the relationship between parents and their children (family). This relationship begins in the womb, continues with the birth process and takes care of the child.The method used in writing this journal is a qualitative descriptive method with a literature study and literature review approach. The steps taken when writing this topic include researching and reading various references such as books, magazines and online news portals related to this topic. Next, the author will explain and explain comprehensively. Then, the author draws conclusions and explains from the perspective of Christian ethics.The research results show that elderly people have various problems, resulting in different efforts or steps in each aspect of problems in life. Elderly people must try to remain active in their daily activities (for example: worship, social gathering, elderly exercise, hobbies), prepare health costs, arrange visits and recreation schedules with children and grandchildren, and receive support and love from family, neighbors and more relatives. easily prevent feelings of loneliness and fear of death.